MODELLING AND ANALYSIS OF AN URBAN ROAD TRAFFIC NOISE POLLUTION (CASE STUDY OF AN INTERRUPTED FLOW TRAFFIC NOISE AT A SIGNALIZED INTERSECTION): Modelling and Analysis of an Urban Road Traffic Noise Pollution - Forouhid, Amir Esmael; Falah Zadeh, Amir; Mahmoudi, Jafar (Journal of Applied Engineering Science, 2021)
This research aimed at modeling interrupted flow traffic noise at a signalized intersection. In this study, a new approach has been used with SPSS and Arc GIS with urban road traffic noise. The measured parameters of noise include noise equivalent level, volume of light vehicles, heavy vehicles and time mean speed. The results showed that the Spearman correlation coefficient between the interface and the level of the noise at morning, evening and total time were 0.241, 0.35 and 0.45. The spearman correlation coefficient between the interface of the buildings and the intersection of all types of vehicles passing through the morning, evening and total time equal to 0.534, 0.328 and 0.409. The results showed that noise level can be predicted through the speed variables of the vehicles, the volume of vehicles passing heavy and the use of land use of buildings. According to the results and the noise maps for the modeling noise of the estimated coefficients from the equation, it can be found that in building highway in urban, closer look on internationally acting Green Building Labels and noise protection is seen as an important part of the social sustainability aspects of a building.
Keywords: Noise pollution; Vehicles; Sustainability; Regression, Road traffic.